Al-Qur’an dan Tantangan Society 5.0 - Syarif Hidayat (STAI Terpadu Yogyakarta, 2020)
This paper seeks to review general problems regarding the development of forms, technical and interpretive functions that should exist and be developed for the use of the Koran in facing Society 5.0, some of the problems faced are related to efforts to change the form of the Koran and efforts to maintain the authenticity of al-Qur'an from changes in form and technical functions as a result of the development carried out in facing society 5.0. Society 5.0 is a challenge for future commentators who must present the Koran as Rahmatan lil 'Alamin. The existence of the principle of Artificial Intelligence in the development of Society 5.0 requires that the commentators, observers of the Koran, must not be careless in following the developments of the Age. The development of the function of access to the Koran must always be endeavored by Muslim scientists with the scientific field of the Koran, because future Muslims increasingly need a variety of uses and functions of smart software and hardware for their daily needs. -day. The problems that will be faced and demand attention from scientists in the field of the science of the Koran to find a solution include the absence of clear references to the al-Qur'an text on the application tool and the al-Qur'an website to be developed, incomplete signs read especially shakal which can trigger the development of differences in understanding, the possibility of data input errors (human error), and the possibility of content irregularities, especially from outside. Efforts that must be made to overcome the above problems include controlling the writing, improving and maintaining the security system and updating and checking data regularly.